Mechanical characterization of the Amazonian Pomacea dolioides (Reeve, 1856) shell - Andrade F., Ariana; Nogueira B., Rodrigo (Instituto de Ecología, A.C., 2018)
We investigated the mechanical behavior of freshwater mollusk shells, Pomacea dolioides, collected from a floodplain area located in Amazonas, Brazil. With the purpose of characterizing the mechanical properties of the shells, bending, hardness and roughness tests were carried out. To determine the shell flexural strength, a new methodology was proposed for the calculation of it, considering the curved geometry of the specimens taken from the shells. It was also described the mechanical properties as a function of shell position and thickness, variation of the surface hardness along the shell and the low level of superficial irregularity in the inner layer of the shells. Shell presented a mean flexural rupture modulus (MOR) of 128.0 MPa, Rockwell HR15N hardness = 50 ± 8.3 and a low level of irregularities in the inner layer, roughness Ra = 0.160 μm.